2021
DOI: 10.3390/nu13072377
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Considering Malnutrition and Sarcopenia in Order to Improve the QOL of Elderly Hemodialysis Patients in Japan in the Era of 100-Year Life

Abstract: In the current aging society of Japan, malnutrition and resultant sarcopenia have been widely identified as important symptomatic indicators of ill health and can cause impairments of longevity and quality of life in older individuals. Elderly individuals are recommended to have sufficient calorie and protein intake so as to enjoy a satisfactory quality of life, including maintaining activities of daily living in order to avoid emaciation and sarcopenia. The prevalence of emaciation and sarcopenia in elderly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 73 publications
2
14
0
1
Order By: Relevance
“…Consistently, previous studies found that malnutrition was significantly associated with sarcopenia in patients with MHD ( 26 ). With regard to the indicators used for nutritional assessment, studies have shown that the GNRI ( 27 ) and MIS ( 10 ) were associated with sarcopenia in patients with MHD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistently, previous studies found that malnutrition was significantly associated with sarcopenia in patients with MHD ( 26 ). With regard to the indicators used for nutritional assessment, studies have shown that the GNRI ( 27 ) and MIS ( 10 ) were associated with sarcopenia in patients with MHD.…”
Section: Discussionsupporting
confidence: 89%
“…First, it highlights that screening poor nutrition status is usually highly predictive of sarcopenia in patients with MHD. Second, it is strongly recommended to maintain sufficient calorie and protein intake especially physical therapy to avoid or reverse sarcopenia ( 26 ). However, efforts to increase food intake in patients with MHD with sarcopenia often are unsuccessful because of the persistent anorexia arising from sarcopenia-related inflammatory status ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is an emerging complication associated with quality of life and mortality in patients undergoing long-term PD [18,19]. Although the muscle-bone interaction is complex and the associations are not fully understood, previous studies have shown that the interaction between muscle and bone is mediated by mechanical stresses or paracrine effects by secretory mediators [6,[20][21][22]. Consequently, muscle health is directly or indirectly helpful in maintaining BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle mass is closely related to the bone both anatomically and physiologically, and recent studies have shown that muscle mass or strength is associated with bone health and vice-versa [5,6]. Stretching of muscles places a load on bones to which muscles are attached, and such mechanical stresses increase the cortical bone thickness.…”
Section: Introductionmentioning
confidence: 99%
“…With both the elongation of hemodialysis (HD) duration resulting from the sophistication of HD technology and the increasing age at the time of HD initiation due to the aging society of Japan, the mean age of prevalent HD patients is increasing at an accelerating rate [ 1 ]. Along with the aging of HD patients, presymptomatic conditions such as malnutrition, frailty, sarcopenia, and inflammation have been focused on as important states to help to improve the condition of patients, both those living independently and those requiring physical support or nursing care [ 1 , 2 ], as in the general elderly population. In addition, it should be emphasized that such presymptomatic conditions can often act as a trigger, causing critical events, such as cardiovascular disease (CVD), falls, and fragile fractures, which significantly impair quality of life (QOL) [ 1 ].…”
mentioning
confidence: 99%